Czech Equivalents of Non-finite Verb Forms in the Transaltion of A.C.Doyle's, The Hound of the Baskervilles - Zagrapanová, Ivana (Univerzita Pardubice, 2010)
This research paper deals with the topic of English non-finite verb forms. The aim is to classify the non-finite forms and compare their two Czech translations concretely on the work of Sir A.C.Doyle, The Hound of the Baskervilles. The theoretical part firstly introduces the features of the literary style and the aspects of translation and categorizes the non-finite verb forms and their function in the English sentence. The practical part deals with the obtained data and provides the comparison of Czech translations of the non-finite verb forms, their syntactic functions and the frequency of their use in the text.
České ekvivalenty neurčitých slovesných tvarů v překladu knihy A.C.Doyla, Pes Baservillský
Keywords: neurčité slovesné tvary; literární styl; překlady; Doyle, Arthur Conan; non-finite verb forms; literary style; translations